The Ecofriendly Biosorbent of Methylene Blue Using Banana Peels Waste - Susanti, Indri; Iqbal, Rendy Muhamad; Sholeha, Novia Amalia; Putri, Khusnul Fatimah (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
This research aimed to synthesize and characterize the properties of green banana peel waste to be used as adsorbent material. The green banana peel waste was prepared by sieved to be banana powder and then characterized by XRD, FTIR, XRF, and TGA. The adsorption capacity of methylene blue was tested using a simple method, the “batch method”, with further analysis by spectrophotometry UV-Vis. The XRF results of green banana peel showed that most of the composition is potassium and phosphorus. The methylene blue adsorption capacity of banana peel material is up to 75.10% with 0.5 grams of adsorbent, which is more significant than in the banana peel, which is 68.04% with 0.2 grams.